Introduction to horticultural science - Arteca, Richard N. (Cengage Learning, 2014)
Designed to provide readers with a full appreciation of the wonderful world of horticultural science, the Second Edition of INTRODUCTION TO HORTICULTURAL SCIENCE covers everything the reader needs to know in a comprehensive format that is easy to understand. Coverage includes critical topics such as fundamental concepts, cutting edge research, careers in horticulture, the relationship between horticulture and the environment, classification of plants, and plant anatomy. Readers are also introduced to key concepts such as plant propagation, media, nutrients and fertilizers, plants and the environment, plant growth regulators, post harvest physiology and pest management, greenhouse structures, nursery site selection, development and facilities, producing nursery crops, and floral design. Through enhanced visual aids and the inclusion of recent trends in the field, the second edition has been designed to peak reader interest and improve reader understanding.